2023
DOI: 10.1051/e3sconf/202337201012
|View full text |Cite
|
Sign up to set email alerts
|

Optimization design of real-time scheduling scheme for city bus vehicles based on BP neural network

Abstract: Urban public transportation is inseparably related to people’s travel and life. Prioritizing the development of public transportation is a major national policy proposed by the Chinese government, especially to actively promote the development of intelligent public transportation systems. Developing and building advanced intelligent public transport operation and scheduling management system, designing efficient, flexible and low-cost operation and scheduling mode, improving the management level and service qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Studies have found that the government's role is crucial in enhancing the service quality of public transportation (Prabowo et al, 2019). Governments have also suggested prioritizing the development of public transportation as a major national policy to actively encourage the development of intelligent public transportation systems (Xu et al, 2023). Furthermore, recent laws aim to determine a new division of responsibilities within public administration systems for the planning, implementation, and financing of public transport, emphasizing the importance of government involvement in transportation systems (Augustyn, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that the government's role is crucial in enhancing the service quality of public transportation (Prabowo et al, 2019). Governments have also suggested prioritizing the development of public transportation as a major national policy to actively encourage the development of intelligent public transportation systems (Xu et al, 2023). Furthermore, recent laws aim to determine a new division of responsibilities within public administration systems for the planning, implementation, and financing of public transport, emphasizing the importance of government involvement in transportation systems (Augustyn, 2020).…”
Section: Introductionmentioning
confidence: 99%